Peningkatan Aktivitas Dan Hasil Belajar PAIDBP Siswa Kelas IV Sekolah Dasar Melalui Penggunaan Model Discovery Learning - Fitria Aini; Yusrizal Efendi; Mega Adyna Movitaria (Program Studi PGMI STAI Daruttaqwa Gresik, 2021)
This article to improve PAIdBP learning activities and learning outcomes for Class IV students of UPTD SDN 02 Simpang Kapuak for the 2020/2021 academic year by using the Discovery Learning model. This article is a Classroom Action Research (CAR) which was carried out in 2 cycles with 2 meetings for each cycle. The subjects in this study were grade IV students of UPTD SDN 02 Simpang Kapuak for the academic year 2020/2021, totaling 20 people. The data in this study were obtained through the use of observation sheets for teacher and student activities during the learning process and student learning outcomes at the end of each cycle. The data generated in this study were processed and analyzed descriptively qualitatively. The conclusion of the study shows that the use of the Discovery Learning model with the correct steps can increase the activity by an average of 78,78 and learning outcomes of Class IV PAIdBP students become 95% UPTD SDN 02 Simpang Kapuak Academic Year 2020/2021.